Language Harmony: Analysis of the Influence of Arabic Children's Songs in the Formation of Early Childhood Language - Rosyada, Amrina; Aula, Iqbal Ahsanul (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
The process of language acquisition in children is not always immediate. There are various ways through which language can be learned, such as through familial interactions or exposure to music. Research indicates that music, including children's songs, plays a role in enhancing cognitive and language development in young children. This study investigates how Arabic children's songs can positively impact early language skills. Specifically, it aims to examine the influence of Arabic children's songs on language development during early childhood. The research was conducted using qualitative research methods with a descriptive approach. The type of research used is descriptive qualitative research. Data were collected from primary and secondary sources through observation and interviews. The analysis technique used the Miles and Huberman model which consists of 4 stages, namely: (1) data collection, (2) data reduction, (3) data presentation, and (4) decision making or verification. The findings suggest that Arabic children's songs significantly contribute to early language development. The rich vocabulary present in these songs serves as a beneficial stimulus for children, aiding in their language acquisition process. Moreover, Arabic children's songs have the potential to boost children's motivation to learn and accelerate their language skills in an enjoyable and interactive manner.